Wei shixian "sige xiandaihua" er nuli fendou :
'Struggle energetically to realize the "Four modernizations" : Second of four propaganda posters in commemoration of the twentieth anniversary of Chairman Mao's instruction to "organize contingents of the people's militia on a big scale"'.